Tingkat Kecemasan Belajar pada Peserta Didik yang Memiliki Prestasi Akademik Rendah di Kelas X SMK Negeri 4 Palembang - Wijaya, Mukti; Sofah, Rahmi; Hakim, Imron A (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2019)
The study was conducted with the aim to determine the level of learning anxiety of students who have low academic ability in class X Palembang N 4 SMK. This study uses a survey method with a quantitative approach. The population in this study were students who had low academic ability with a number of 85 and a sample or respondent of this study that was 85 students using purposive sampling. Date collection techniques use a percentage count. Aspects measured by learning anxiety in students who have low academic ability in class X of SMK N 4 Palembang, namely, physical, emotional, and mental or cognitive. The results of date analysis showed that the level of learning anxiety in students who had low academic ability in class X junior high school 4 Palembang, 35% in the very low category (SR), 49% in the low category (R),16% in the high category (T), and 0% in the very high category (ST).